1990
DOI: 10.1111/j.1464-410x.1990.tb14898.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Symptoms in Men Aged over 60

Abstract: The prevalence of urological symptoms in elderly males in the community is poorly documented. A series of 578 men, aged 60 to 85 years and registered with one inner city health centre, completed a self-administered questionnaire which inquired about current urological symptoms. Many symptoms were common, including a lengthening of the time to pass urine (26%), a deterioration in urinary flow (30%), dribbling (26%), urgency (31%), increased day-time frequency (32%) and nocturia (57%); 102 men (18%) gave 5 or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
7

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 3 publications
0
19
0
7
Order By: Relevance
“…1 that about half the patients clearly had an abnormally large NUP on almost all the nights recorded and were subsequently classified as having nocturnal polyuria, although no clear definition of this term has been published. It has been known for many years that increasing age is associated with increasing nocturnal symptoms such as nocturia [ 6, 10, 11, 18]. It has also been shown that the whole population of the elderly has a diminished circadian rhythm of urine production [ 19], but the direct relationship between nocturnal symptoms and urine production has not been fully clarified [ 9–11, 20].…”
Section: Discussionmentioning
confidence: 99%
“…1 that about half the patients clearly had an abnormally large NUP on almost all the nights recorded and were subsequently classified as having nocturnal polyuria, although no clear definition of this term has been published. It has been known for many years that increasing age is associated with increasing nocturnal symptoms such as nocturia [ 6, 10, 11, 18]. It has also been shown that the whole population of the elderly has a diminished circadian rhythm of urine production [ 19], but the direct relationship between nocturnal symptoms and urine production has not been fully clarified [ 9–11, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of desmopressin for nocturia (waking to void at night) was investigated in a large scale study [1]. In clinical practice most patients with nocturia are likely to be elderly, because the prevalence of nocturia increases with age [2][3][4][5][6][7][8][9][10][11]. The safety profile established in children and adults cannot be directly transferred to the elderly as, in general, they have more concomitant diseases and use more drugs than do younger subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Despite seemingly high rates of prevalence of BPH, several studies have reported that urologists see only a fraction of men with clinical symptoms often associated with, although not indicative, of BPH (e.g. urgency, frequency and nocturia), and that many more men may be in need of further assessment and treatment [ 4, 8]. Drummond et al [ 9] further suggested that the main burden of BPH is manifested as a reduction in quality of life (QoL) and is not reflected in the consumption of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%